Assessment of land use and land cover changes and their impact on land surface temperature in Greater Accra, Ghana - Dennis Ngminmaale Gyile; Austin Asare; Augustine Prosper Osei-Gyabaah; David Anaafo (Scientific African, 2025)
Urban sprawl within the Greater Accra Metropolitan Area has led to an increase in land-surface temperature (LST) by 4.07 °C since 1991, exacerbating the urban heat island (UHI) phenomenon and heightening health and energy challenges associated with heat. Our study evaluated the influence of land use and land cover change (LULCC) on LST by implementing supervised classification techniques on multi-temporal imagery from Landsat Thematic Mapper (TM), Enhanced Thematic Mapper Plus (ETM+), and Operational Land Imager / Thermal Infrared Sensor (OLI/TIRS) for the years 1991, 2002, 2015, and 2020. The classification achieved an overall accuracy exceeding 85 % and a Cohen’s kappa of over 0.80. Thermal patterns were examined using non-parametric analysis of variance (ANOVA) and Spearman’s correlation analysis. The proportion of built-up land surged from 30.63 % in 1991 to 72.53 % in 2020, primarily at the expense of forested areas, which decreased from 21.35 % to 11.35 %. The mean urban LST increased by 4.07 °C, with built-up areas recording the highest temperatures; unexpectedly, water bodies also exhibited elevated LST, likely attributed to pollution and their shallow nature. LST showed a negative correlation with the normalized difference vegetation index (NDVI) and positive correlations with the normalized difference built-up index (NDBI), bare-soil index (BSI), modified normalized difference water index (MNDWI), and normalized difference bareness index (NDBAL). These stable correlations across all assessed years indicate that rapid LULCC, rather than inter-annual climate variability, is the primary driver of surface warming in Accra.